Akromegalie: současný pohled - Kršek, Michal (Vnitrni lekarstvi, 2015)
Acromegaly is a rare disorder caused by autonomous oversecretion of growth hormone mostly by pituitary adenoma. Untreated acromegaly leads to significantly increased morbidity and mortality and impaired quality of life. Early diagnosis and treatment is therefore essential for improvement of patients prognosis and management of acromegaly should be concentrated in specialized centres. Present article summarizes current view on diagnosis and treatment of acromegaly.
Keywords: nemocnice speciální; akromegalie; nádory hypofýzy; Humans; Acromegaly; časná diagnóza; Quality of Life; lidé; kvalita života; Hospitals, Special; Pituitary Neoplasms; Male; prognóza; adenom; Adenoma; Early Diagnosis; Early Medical Intervention; časná lékařská intervence; mužské pohlaví; Prognosis